Bio‐Oil as a Potential Biomass‐Derived Renewable Raw Material for Bio‐Phenol Production. Issue 5 (14th April 2018) - Zhu, Lijuan; Jin, Feng; Fan, Minghui; Liu, Junxu; Chang, Rui; Jia, Qifang; Tang, Chi; Li, Quanxin
Abstract: A route for directional conversion of bio‐oil into phenol by means of coupling the catalytic cracking of the bio‐oil with the hydroxylation of the bio‐oil‐based benzene‐rich aromatics is proposed. High selectivity for phenol in the resulting organic liquid was achieved, with an almost complete conversion of the bio‐oil. Co‐cracking of the bio‐oil with methanol over a Zn‐modified zeolite significantly enhanced the yields of aromatics and decreased the deactivation of the catalyst during the catalytic cracking of the bio‐oil. The phenol yield depended on the metal oxide catalysts, the temperature, and the reaction time during hydroxylation of the benzene‐rich aromatics. The reaction pathway of converting bio‐oil into phenol was elucidated based on the products identified and the characterization of the catalysts. Abstract : Directional production of the renewable high‐value biochemical phenol from bio‐oil was achieved by coupling the catalytic cracking of bio‐oil into aromatics with the dealkylation of heavier aromatics to benzene and the hydroxylation of benzene‐rich aromatics to phenol. High phenol selectivity with an almost complete conversion of the bio‐oil was obtained.